Unveiled diversity: Amazonian Campinaranas harbor twice the number of bryophyte species recorded in the last century - Cerqueira, Gabriela Ramos; Sierra, Adriel M.; Ilkiu-Borges, Anna Luiza; Mota-de-Oliveira, Sylvia; Zartman, Charles Eugene (Acta Botânica Brasílica, 2021)
ABSTRACT Campinaranas are unique vegetation patches in the Amazonian biome, characterized by white-sand soils with relatively low nutrient content and subject to periodic flooding coupled with fluctuating groundwater levels. This study aimed to produce a synopsis of the bryophyte flora in Campinarana habitats by combining information from the literature with new collections made in the Uatumã Sustainable Development Reserve (Balbina, Central Amazonia), and areas of the middle Uaupés river (São Gabriel da Cachoeira, upper Rio Negro). One hundred and forty-three species were identified among mosses and liverworts, of which 68 are reported for the first time in Campinaranas. The species Frullania rio-janeirensis, Ceratolejeunea filaria, Diplasiolejeunea cobrensis and Bazzania diversicuspis are new records for the state of Amazonas. These results reveal high species richness for Campinaranas and indicate the need for continued study in this underexplored Amazonian habitat. This study emphasizes the importance of carrying out floristic inventories in poorly known environments and of further studies with different approaches, such as ecological, phytogeographic and genetic efforts.